Factors That Influence The Value of Sukuk in Indonesia - Gafur, Abdul; Muhammad, Muhammad; Ansharullah, Ansharullah (Jurnal Ekonomika dan Bisnis Islam, 2023)
This study aims to determine the effect of the consumer price index, BI rate, Rupiah exchange rate, money supply, and Gross Domestic Product growth on the value of government sharia securities(SBSN)  and corporate sukuk in Indonesia. The type of research used is quantitative research with the Error Correction Model (ECM) approach as a data analysis tool. The results showed that partially the short-term and long-term consumer price index variables had a significant effect on government sharia securities, but did not have a significant effect on corporate sukuk. Where if the CPI increases, it will be followed by a decrease in the value of securities issued by the government. In contrast to BI interest rates on SBSN and corporate sukuk which do not have a significant short-term effect, but have a significant long-term effect. Where if interest rates increase, investors will reduce their investment. Conversely, if interest rates decrease, investors will increase their investment. This is done to minimize the risks that will arise In the short term and long term. Meanwhile, the money supply has a significant effect on SBSN and corporate sukuk. This is because SBSN and corporate bonds are closely related to the growth of the amount of money circulating in the community. Meanwhile, the Rupiah exchange rate and Gross Domestic Product growth have no significant effect on SBSN and corporate sukuk in the short and long term. This is because these two variables do not show any relationship with the SBSN and corporate sukuk variables.